1998
DOI: 10.2135/cropsci1998.0011183x003800050015x
|View full text |Cite
|
Sign up to set email alerts
|

Grain Yield Increase in Recent Argentine Wheat Cultivars

Abstract: This study analyzes differences in potential yield among six semidwarf awned spring bread wheat (Trilicum aestivum L.) cultivars recently selected in Argentina. Yield was considered as the product of number of grain per square meter (NG) and weight per grain. The NG was analyzed in terms of (i) duration of the inflorescence growth period (excluding grains), (ii) crop growth rate during that period, (iii) partitioning of crop dry matter to spikes during the same period, and (iv) grain/spike weight ratio (i.e., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
121
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(138 citation statements)
references
References 0 publications
14
121
2
1
Order By: Relevance
“…On the other hand, for a given genotype, Fischer (2007) demonstrated under controlled conditions that F s was quite stable across different total assimilation amounts, and even different potential spike sizes, as caused by early photoperiod effects on spikelet number. Abbate et al (1998) found only small differences in F s (range 0.29-0.34) among modern semi-dwarf Argentine cultivars. Reynolds et al (2001) reported that the GN advantage associated with LR19 from Agropyron was associated with a proportional increase in F s .…”
Section: Grain Numbermentioning
confidence: 65%
See 3 more Smart Citations
“…On the other hand, for a given genotype, Fischer (2007) demonstrated under controlled conditions that F s was quite stable across different total assimilation amounts, and even different potential spike sizes, as caused by early photoperiod effects on spikelet number. Abbate et al (1998) found only small differences in F s (range 0.29-0.34) among modern semi-dwarf Argentine cultivars. Reynolds et al (2001) reported that the GN advantage associated with LR19 from Agropyron was associated with a proportional increase in F s .…”
Section: Grain Numbermentioning
confidence: 65%
“…Following Eqn 1, D s did not vary in a tall versus short isogenic comparison (see references in Fischer 2007) nor in the comparison of modern Argentine wheats (Abbate et al 1998), so apart from Serrago et al (2008) above, cultivar effects on D s have yet to be described. However, large Argentine cultivar differences in the duration of the phase (TS/SE to AN) in 8C (at least 2-fold for a given photoperiod) were reported by Whitechurch et al (2007), and these may reflect differences in D s , which falls largely within TS/SE to AN.…”
Section: Grain Numbermentioning
confidence: 98%
See 2 more Smart Citations
“…This strong association between number of grains per unit area and yield would indicate that the supply of assimilates for grain growth (source capacity), along with the reserves accumulated in the vegetative organs, at pre-anthesis stage, were enough to meet the demand of developing grains (sink capacity). The high number of grains per square meter and a sufficient production of assimilates to produce additional grains could be a result of a longer spike development period at pre-anthesis (Calderini & Reynolds, 2000), higher crop growth rate during that period, greater partitioning to spikes or more grains per weight of spikes (Abbate et al, 1998). However, the ability of changing the morphogenetic pattern within the spike, thus favoring the development of a higher number of grains per spike, that have been attributed to the gene Rht (Waddington et al, 1986), could also have contributed.…”
Section: Resultsmentioning
confidence: 99%